Mineralization events in the Xiaokele porphyry Cu (–Mo) deposit, NE China: Evidence from zircon U–Pb and K‐feldspar Ar–Ar geochronology and petrochemistry. Issue 3 (30th March 2020) - Sun, Yonggang; Li, Bile; Sun, Fengyue; Ding, Qingfeng; Wang, Baiyi; Li, Yujin; Wang, Kun
Abstract: The Great Xing'an Range (GXR), Northeast (NE) China, is a major polymetallic metallogenic belt in the eastern segment of the Central Asian Orogenic Belt. The newly discovered Xiaokele porphyry Cu (–Mo) deposit lies in the northern GXR. Field geological and geochronological studies have revealed two mineralization events in this deposit: early porphyry‐type Cu (–Mo) mineralization, and later vein‐type Cu mineralization. Previous geochronological studies yielded an age of ca. 147 Ma for the early Cu (–Mo) mineralization. Our 40 Ar/ 39 Ar dating yielded 40 Ar/ 39 Ar plateau ages of 124.8 ± 0.4 to 124.3 ± 0.4 Ma on K‐feldspar in altered Cu‐mineralized diorite porphyrite dikes that represent the overprinting vein‐type Cu mineralization, consistent with zircon U–Pb ages of the diorite porphyrite (126.4 ± 0.5 to 125.0 ± 0.5 Ma). The Cr and Ni contents and Mg # of the Xiaokele diorite porphyrites are high. The diorite porphyrites at Xiaokele are enriched in light rare‐earth elements (REEs), and large‐ion lithophile elements (e.g., Rb, Ba, and K), are depleted in heavy REEs and high‐field‐strength elements (e.g., Nb, Ta, and Ti), and have weak negative ε Hf ( t ) values (+0.29 to +5.27) with two‐stage model ages (TDM2 ) of 1, 164–845 Ma. Given the regional tectonic setting in Early Cretaceous, the ore‐bearing diorite porphyrites were likely formed in an extensional environment related to lithospheric delamination and asthenospheric upwelling induced by subduction of the Paleo‐Pacific Plate. These tectonic events caused large‐scale magmatic activity, ore mineralization, and lithospheric thinning in NE China. Abstract : The newly discovered Xiaokele porphyry Cu (–Mo) deposit lies in the Great Xing'an Range, NE China. In this work, we have revealed two mineralization events in this deposit, including early porphyry‐type Cu (–Mo) mineralization and later vein‐type Cu mineralization. This deposit were likely formed in an extensional environment related to lithospheric delamination and asthenospheric upwelling induced by subduction of the Paleo‐Pacific Plate during the Early Cretaceous.